2014
DOI: 10.1155/2014/703930
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Tissue Distribution of Duck Tembusu Virus in Adult Ducks

Abstract: In 2010, a novel Tembusu virus (TMUV) that caused a severe decrease in the egg production of ducks was isolated in southeast China. Given the novelty of this duck pathogen, little information is available regarding its pathogenesis. Here, we systematically investigated the replication kinetics of TMUV PTD2010 in adult male and female ducks. We found that PTD2010 was detectable in most of the parenchymatous organs as well as the oviduct and intestinal tract from days 1 to 7 after inoculation. Viral titers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Obviously, the expression levels of goose IFITM1 and IFITM3 displayed an upward trend in all the tested tissues, especially the cecum (Figure 7), where TMUV was primarily distributed (Figure 8). High viral copy numbers were also observed in the intestinal tract tissues of TMUV-infected ducks [48]. In addition, goose IFITM1 was intensively transcribed in the TMUV-infected spleen and thymus (Figure 7), where the significant upregulation of the IFNs was previously observed [48].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Obviously, the expression levels of goose IFITM1 and IFITM3 displayed an upward trend in all the tested tissues, especially the cecum (Figure 7), where TMUV was primarily distributed (Figure 8). High viral copy numbers were also observed in the intestinal tract tissues of TMUV-infected ducks [48]. In addition, goose IFITM1 was intensively transcribed in the TMUV-infected spleen and thymus (Figure 7), where the significant upregulation of the IFNs was previously observed [48].…”
Section: Discussionmentioning
confidence: 62%
“…High viral copy numbers were also observed in the intestinal tract tissues of TMUV-infected ducks [48]. In addition, goose IFITM1 was intensively transcribed in the TMUV-infected spleen and thymus (Figure 7), where the significant upregulation of the IFNs was previously observed [48]. After TMUV infection, the virus was intensively located in the collected tissues, which reasonably explains why higher expression levels of goose IFITM1 and IFITM3 appeared in the TMUV-infected gosling tissues than those of the mock-infected group.…”
Section: Discussionmentioning
confidence: 93%
“…Under natural conditions, a variety of birds including ducks, chickens, and geese are at risk of DTMUV [8], affecting their growth and production [4]. DTMUV is an RNA virus with a single strand and positive-sense, which produces pathogenicity similar to that of other Flaviviruses [32]. It is well known that Flaviviruses, such as JEV, infect multiple cell types and have the capability to employ various endocytic pathways for entry into cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which DTMUV kill susceptible cells and ultimately produce diseases in birds or other animals [3,12] remain poorly understood. In this study, we demonstrated that DTMUV possesses the ability to replicate not only in natural primary host cells but also in mammalian cell lines, and that DTMUV-infected cells display morphological and biochemical changes consistently associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%